2019
DOI: 10.1038/s41598-019-49609-9
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine produces oxidative stress and alters mitochondrial function in human neuron-like cells

Abstract: Atomoxetine (ATX) is a non-stimulant drug used in the treatment of attention-deficit/hyperactivity disorder (ADHD) and is a selective norepinephrine reuptake inhibitor. It has been shown that ATX has additional effects beyond the inhibition of norepinephrine reuptake, affecting several signal transduction pathways and alters gene expression. Here, we study alterations in oxidative stress and mitochondrial function in human differentiated SH-SY5Y cells exposed over a range of concentrations of ATX. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Atomoxetine hydrochloride, which was prescribed for 18.0% of the study subjects, has been reported to cause mitochondrial dysfunction when used at high concentrations [25]. Therefore, it is considered highly necessary to assess oxidative stress using objective biomarkers for selecting the appropriate drug dose.…”
Section: Discussionmentioning
confidence: 99%
“…Atomoxetine hydrochloride, which was prescribed for 18.0% of the study subjects, has been reported to cause mitochondrial dysfunction when used at high concentrations [25]. Therefore, it is considered highly necessary to assess oxidative stress using objective biomarkers for selecting the appropriate drug dose.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, it was demonstrated that ATX treatment increases extracellular catecholamine levels [ 22 , 72 ]. Therefore, ATX can trigger an increase of cytosolic and mitochondrial ROS, producing damage to the mitochondria and consequently, cell death [ 80 ]. The precise association between the auto-oxidation of catecholamines and the generation of oxidative stress in ADHD remains unclear.…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…On the other hand, it has been shown that dopamine and norepinephrine can easily undergo auto-oxidation, forming ROS [125,126], which could lead to cell damage and damage to DNA [127,128]. Also, it has been shown that ATX treatment increases extracellular norepinephrine and dopamine levels [19,129], which would produce an increase in oxidative stress and, as a consequence, cell damage and mitochondrial dysfunction [130]. The brain is particularly susceptible to oxidative stress because of its high lipid content and the high demand for energy consumption [131].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 99%